Game-based collaborative vocabulary learning in blended and distance L2 learning. (2nd October 2022) - Bahari, Akbar
ABSTRACT: Adopting the focus on form (FonF) practice model, the effectiveness of game-based collaborative vocabulary learning (GBCVL) was tested as a tool to develop vocabulary size and depth with a focus on dynamicity and nonlinearity of second language (L2) learner motivation. To improve the measures, a mixed-methods approach was used on a sample of 95 English as a foreign language (EFL) intermediate learners, who individually selected and played games for two consecutive terms with respect to their nonlinear dynamic motivational factors at the individual level. Drawing on the FonF practice model, the phonological, grammatical, and lexical forms of the motivationally selected materials were emphasized and contextualized as the treatment to find out their relationship with vocabulary size and depth. The obtained results showed a significant relationship between playing vocabulary games and developing vocabulary size and depth. The effectiveness of the GBCVL at benefiting from the potential behind computer-assisted language learning (CALL) affordances towards vocabulary learning goals while catering for nonlinear and dynamic motivational factors at the individual learner level was the main pedagogical implication of the present study.